Pengaruh Pemberian Terapi Titik Tekan (Akupresur) Dalam Mengurangi Post Operative Nausea And Vomiting (PONV) Pada Pasien Dengan Anestesi Spinal Di RSI Sultan Agung Semarang - Ningsih, Nur Andriani; Setyowati, Anita; Dewi, Ratih Kusuma (Borneo Nursing Journal (BNJ), 2026)
Background: Postoperative Nausea and Vomiting (PONV) is one of the most common complications following surgical procedures performed under spinal anesthesia. This condition can cause discomfort, delay recovery, and increase the risk of postoperative complications. One non-pharmacological intervention that may help reduce PONV is acupressure therapy, particularly stimulation of the Pericardium 6 (P6) acupressure point. Objective: This study aims to determine the effect of acupressure therapy on reducing the incidence of Postoperative Nausea and Vomiting (PONV) among patients undergoing spinal anesthesia at RSI (Islamic Hospital) Sultan Agung, Semarang. Methods: This study employed a pre-experimental design using a onegroup pretest–posttest approach. A total of 57 respondents were selected through purposive sampling. Data were collected using an observation checklist to assess the incidence of Postoperative Nausea and Vomiting (PONV) before and after the intervention. Data analysis was conducted using the Wilcoxon test. Results: The findings showed that before the intervention, most respondents experienced moderate Postoperative Nausea and Vomiting (PONV) (57.9%). After receiving acupressure therapy, the majority of respondents showed improvement, with 86.0% experiencing mild PONV and 8.8% reporting no symptoms of PONV. The results of the Wilcoxon test yielded a p-value of less than 0.05, indicating that acupressure therapy had a statistically significant effect on reducing Postoperative Nausea and Vomiting (PONV). Conclusion: Acupressure therapy had a significant effect on reducing the incidence of Postoperative Nausea and Vomiting (PONV) in patients undergoing spinal anesthesia. Therefore, acupressure may be considered an effective non-pharmacological intervention for managing PONV. Recommendation: Future researchers are encouraged to conduct similar studies using more robust research designs, such as incorporating a control group and a larger sample size. In addition, other variables that may influence the occurrence of Postoperative Nausea and Vomiting (PONV) should be considered to obtain more comprehensive and reliable results.